2005
DOI: 10.1016/j.livprodsci.2004.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparing risk perceptions and risk management in organic and conventional dairy farming: empirical results from Norway

Abstract: This study was conducted to explore organic and conventional dairy farmers' perceptions of risk and risk management, and to examine relationships between farm and farmer characteristics, risk perceptions, and strategies. The data originate from a survey of conventional (n = 363) and organic (n = 162) dairy farmers in Norway. Organic farmers had the least risk averse perceptions. Institutional and production risks were perceived as primary sources of risk, with farm support payments at the top. Compared to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
180
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 18 publications
19
180
1
10
Order By: Relevance
“…This finding matches previous studies of organic farmers in Norway in which they perceived institutional factors as primary sources of risk, especially concerning general and organic farming payments (Flaten et al, 2005). Other highly ranked reasons (overall means higher than 4.75) reflected economic issues.…”
Section: Reasons For Ceasing Certificationsupporting
confidence: 88%
“…This finding matches previous studies of organic farmers in Norway in which they perceived institutional factors as primary sources of risk, especially concerning general and organic farming payments (Flaten et al, 2005). Other highly ranked reasons (overall means higher than 4.75) reflected economic issues.…”
Section: Reasons For Ceasing Certificationsupporting
confidence: 88%
“…A análise dos dados teve como base os procedimentos utilizados por MEUWISSEN et al (2001), FLATEN et al (2005 e BORGES (2010). Em uma etapa inicial, calculou-se a média das relevâncias atribuídas pelos entrevistados às fontes e às medidas de gestão de riscos.…”
Section: Methodsunclassified
“…In addition, they often mistrust insurance firms (Njuguna and Arunga, 2013). Meuwissen et al (2001) discussed relative risk attitude and Flaten et al (2005) studied comparative risk aversion. They found that a farmers' attitude towards risk basically reflects a farmer's willingness to take on risk.…”
Section: Literature Reviewmentioning
confidence: 99%